Evaluating the stability of antibody titres against Leishmania infantum determined by IFAT in long-term stored canine frozen samples - Patricia Olmeda; David Díaz-Regañón; Alejandra Villaescusa; Inmaculada Amusategui; Miguel A. Tesouro; Fernando Rodríguez-Franco; Mercedes García-Sancho; Daniel Martín-Fraile; Ángel Sainz (Parasites & Vectors)
Abstract Background The immunofluorescence antibody test (IFAT) is a serological diagnostic technique used to quantify serum antibodies generated in response to exposure to various pathogens, such as Leishmania infantum. Retrospective analysis of previously collected frozen samples is highly valuable for clinical and research purposes. The primary aim of this study was to evaluate the impact of long-term frozen storage of canine plasma samples on the IFAT-based serological diagnosis of L. infantum exposure. Methods A total of 189 frozen plasma samples from dogs stored at −20 °C for 5, 10 or 20 years, which had previously been tested for L. infantum exposure via IFAT (IgG), were reanalysed to assess the concordance between past and current qualitative and quantitative results. Results The qualitative agreement between the former and current IFATs was 92.1%. The samples from 20 years prior presented the greatest increase in negative samples in the second analysis (from 28.6 to 39.7%). A strong positive correlation was observed between the quantitative measurements of the past and present across all three groups. The exact quantitative agreement was 48.7%. Conclusions The results of this study indicate that freezing at −20 °C is a good technique for prolonged storage of samples for the detection of L. infantum exposure in dogs, as the qualitative IFAT result is not significantly altered. This finding is of particular interest both for clinical endeavours and for future research in this field. Graphical Abstract